If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4z + -1) = 0.25(d + -2) Reorder the terms: 2(-1 + 4z) = 0.25(d + -2) (-1 * 2 + 4z * 2) = 0.25(d + -2) (-2 + 8z) = 0.25(d + -2) Reorder the terms: -2 + 8z = 0.25(-2 + d) -2 + 8z = (-2 * 0.25 + d * 0.25) -2 + 8z = (-0.5 + 0.25d) Solving -2 + 8z = -0.5 + 0.25d Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8z = -0.5 + 2 + 0.25d Combine like terms: -2 + 2 = 0 0 + 8z = -0.5 + 2 + 0.25d 8z = -0.5 + 2 + 0.25d Combine like terms: -0.5 + 2 = 1.5 8z = 1.5 + 0.25d Divide each side by '8'. z = 0.1875 + 0.03125d Simplifying z = 0.1875 + 0.03125d
| 7a-2(a-11)=17 | | 64=-16x^2+64x+0 | | 4r+31=-(2r-1) | | y/3+6=y/2+7 | | 4h+2j-2(4h-3j+2k)= | | 2.9=-13.6-3.5(-4a-1) | | -12=v/5 | | -7k+6k=3 | | 3x-2=7-2x | | 5=n+12 | | m/7=m/14+1/2 | | 3x-1+14-3x=13 | | (4x10^6)(6x10^8)/(8x10^3) | | C=(2+y)h | | 1/2x^2+4x+8 | | f/8+180=209 | | 7x+7y=26.25 | | -2m-6=2m-2(m+2) | | 8x+-6=-6+8x | | 4s=-8 | | -52=t/12-60 | | 11/6z=1/14-4/15 | | -8z+6z=-3z | | 15=2(2+-1) | | -6(x+2)-11=23+8 | | n-n=6+n | | -7a+4(2.5+2a)=13.5 | | 28=7x+11 | | 5q+3q-6+2q=(2+3)+9 | | -1/8p=3/8p | | 4n-8=5n-(n+8) | | 5n+8(6+3n)=164 |